Association of low vitamin C concentrations and low consumption of fresh fruit and vegetables with cardiovascular disease in type 2 diabetes - Anna Toffalini; Nicolò Vigolo; Nicoletta Rolli; Elisa Paviati; Matteo Gelati; Elisa Danese; Giacomo Zoppini (BMC Nutrition)
Abstract Purpose Vitamin C is a fundamental antioxidant with important metabolic actions in several biological processes. Patients with type 2 diabetes (T2D) are exposed to oxidative stress as a consequence of an increased production of reactive oxygen species (ROS). The aims of the present study were to estimate the prevalence of vitamin C deficiency in ambulatory patients with T2D, to study the relationship between vitamin C levels and cardiovascular diseases and to correlate the consumption of fresh fruit and vegetables with vitamin C levels and the presence of cardiovascular diseases. Methods Vitamin C levels, determined by high-performance liquid chromatography (HPLC), and consumption of fresh fruit and vegetables, assessed by a food frequency questionnaire, were measured in 200 outpatients with T2D. All other laboratory variables were measured by standard methods. The association between vitamin C and cardiovascular diseases was assessed by multivariable logistic regression analysis. Results Vitamin C deficiency was found in 12.2% of the subjects. Vitamin C levels and consumption of fresh fruit and vegetables were lower in subjects with cardiovascular diseases. Consumption of fresh fruit and vegetables was associated with higher levels of vitamin C. In the multivariable analysis, vitamin C was independently associated with cardiovascular diseases. Conclusion In conclusion, our study suggests that vitamin C may have an inverse relationship with cardiovascular diseases. Intake of vitamin C from fresh fruit and vegetables could play a protective role.